Hepatitis B virus-related cryoglobulinemia: Clinical characteristics, virological features, and treatment - Hong-xiao Han; Wei Su; Dao-bin Zhou; Jian Li; Xin-xin Cao (Virus Research, 2023)
Background: Hepatitis B virus (HBV) infection is a rare etiology of cryoglobulinemia, and its clinical characteristics, virological features and treatment are poorly understood. Methods: This retrospective study enrolled 23 patients with HBV-related cryoglobulinemia from 497 cryoglobulinemia patients at Peking Union Medical College Hospital between January 2015 and February 2023. We analyzed the clinical characteristics, virological features and management of patients with HBV-related cryoglobulinemia. Results: The 23 patients (13 males; median age 48 years) were all mixed cryoglobulinemia and serological HBsAg positive, while 15 patients exhibited HBV-DNA replication. The presence of HBsAg in cryoglobulins was evaluated in 7 patients, all of whom were positive. The most commonly involved organs were kidneys (69.6%), skin (65.2%), peripheral nerves (21.7%), joints (8.7%), gastrointestinal tract (4.3%), and cardiac (4.3%). Eight patients received antiviral therapy with nucleot (s)ide analogues (NAs) alone, 12 patients received NA- and corticosteroid-based regimens, and 3 patients received NA- and rituximab-based regimens based on the severity of clinical symptoms. After a median follow-up of 44 months, four patients died, and one patient was lost to follow-up. All remaining patients (n = 18) achieved clinical remission, and HBV-DNA replication was not detected in 16 out of 18 patients. There was no HBV reactivation in patients treated with rituximab. The three-year overall survival and progression-free survival were 87.0% and 80.3%, respectively. Conclusions: HBV-related cryoglobulinemia patients should be treated with antiviral therapy. Corticosteroids and rituximab are effective for severe cases, but patients need to be closely monitored for therapy-related infection.